Banking Liquidity Creation & Economic Growth: Two Sides Of The Same Coin - Holloway, Oladisun (2017)
The purpose of this dissertation is to demonstrate the effect of government interventions in the form of capital injection bailout on risk taking by financial institutions, and the knock-on effect this has on economic growth during a period of severe financial stress and recovery. This dissertation will demonstrate this effect of the governmental capital intervention, via the Capital Purchase Program, on banking liquidity creation in the U.S between 2009 Q:1 – 2014 Q:4. The data used is based on the work of Berger & Bouwman (2009) where quarterly call report data are obtained from 2000: Q1 to 2014: Q4. To adjust for inflation, all figures are adjusted using the real 2014: Q4 dollars using the implicit GDP price deflator.